In-plane elasticity of beetle elytra inspired sandwich cores. (15th November 2022) - Yu, Xindi; Zhang, Qicheng; Kontopoulou, Athina; Allegri, Giuliano; Schenk, Mark; Scarpa, Fabrizio
Abstract: The Beetle Elytron Plate (BEP) is a new class of biomimetic sandwich core that features excellent compressive strength, energy absorption capacity and flexural properties. These characteristics make BEPs suitable as potential replacements of classical honeycomb cores in sandwich panels. This work describes the behaviour of the in-plane engineering elastic constants of parametric BEP topologies for the first time. The beetle elytron cores configurations are simulated using Finite Element models, including full-scale models and representative unit cells with periodic boundary conditions for asymptotic homogenization. The models are also benchmarked against experimental results obtained from ASTM tensile tests related to the in-plane Young's modulus, Poisson's ratio and shear modulus. The benchmarked models are then used to perform a parametric analysis against the geometry characteristics of the cellular configurations. Results obtained from this work will provide a solid foundation for further research on BEP structures and expand their applications into wider engineering fields.